Technological Infrastructure and Employee Capacity of Selected Tertiary Institutions in South-South Nigeria - Ikhide, Akhigbe Thompson; Frederick, Ogbeide (NIU Journal of Humanities; Vol. 10 Núm. 2 (2025): NIU Journal of Humanities, Vol. 10 No. 2, June 2025DO - 10.58709/niujhu.v10i2.2205, 2025)
This paper's main goal is to investigate how technological infrastructure affects the development of staff capability in a few South-South Nigerian postsecondary institutions. Examining the connection between staff productivity and organisational structure at a few South-South Nigerian educational institutions is the particular goal. Resource Based Theory (RBT), created by Birge Wenefeldt in 1984, serves as the foundation for this investigation. For the study, a survey research design was chosen. 346 workers were included in the sample, which was taken from a primary source of data. The developed hypothesis was tested using regression analysis. According to the results of the test of the hypothesis, there is a positively significant correlation between employee productivity and organisational structure (F-statistics = 78.1; R-Squared = 0.793, P>0.05). Based on the results, the study came to the conclusion that staff capability and technology infrastructure in South-South Nigerian tertiary institutions are strongly positively correlated. In conclusion, the study suggests that South-South Nigerian tertiary institutions should be well-structured since this would promote staff productivity and capacity building, which may ultimately result in better performance from these institutions. Keywords: Technological Infrastructure, Employee Capacity, Organizational Structure, Employee Productivity, Tertiary Institutions